2018
DOI: 10.1088/1475-7516/2018/04/041
|View full text |Cite
|
Sign up to set email alerts
|

Non-minimally coupled scalar field cosmology with torsion

Abstract: In this work we present a generalized Brans-Dicke lagrangian including a nonminimally coupled Gauss-Bonnet term without imposing the vanishing torsion condition. In the resulting field equations, the torsion is closely related to the dynamics of the scalar field, i.e., if non-minimally coupled terms are present in the theory, then the torsion must be present. For the studied lagrangian we analyze the cosmological consequences of an effective torsional fluid and we show that this fluid can be responsible for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…However, when considering theories with nonminimal couplings or second-order terms in the Lagrangian, in general, φ and torsion's evolution get completely interrelated; see, for instance, refs. [36,37,112,114].…”
Section: Summary and Commentsmentioning
confidence: 99%
“…However, when considering theories with nonminimal couplings or second-order terms in the Lagrangian, in general, φ and torsion's evolution get completely interrelated; see, for instance, refs. [36,37,112,114].…”
Section: Summary and Commentsmentioning
confidence: 99%
“…When V = const., this last term becomes a topological invariant proportional to the Euler characteristic and does not contribute to the field dynamics in the bulk, although it becomes relevant in the regularization of Noether charges for asymptotically locally anti-de Sitter spacetimes [82,83]. In the general case, namely V = const., this term contributes to the field equations acting as a source of torsion [51,[58][59][60][61][62][63][64]66]. The particular nonminimal coupling with the GB term we use is but one choice; the results regarding the speed of GWs are still valid even if the 1/ (Λ + κ 4 V ) coupling is replaced by an arbitrary function of (the magnitude of) the scalar field, f (|φ|).…”
Section: Scalar-tensor Model With Gauss-bonnet Couplingmentioning
confidence: 99%
“…When scalar fields are coupled to the Nieh-Yan topological invariant [52], a regularization procedure of the axial anomaly in RC spacetimes can be prescribed [53][54][55][56][57], and a torsion-descendent axion that might solve the strong CP problem in a gravitational fashion is predicted [58][59][60]. The nonminimal coupling to the Gauss-Bonnet invariant, on the other hand, can be motivated from dimensional reduction of stringgenerated gravity models [61], and it could drive the latetime acceleration of the Universe in the absence of the cosmological constant [62][63][64]. The first-order formulation of Chern-Simons modified gravity produces interesting phenomenology when coupled with fermions [65], and it has been shown that the different nonminimal couplings support four-dimensional black string configurations in vacuum, possessing locally AdS 3 × R geometries with nontrivial torsion [66].…”
Section: Introductionmentioning
confidence: 99%
“…First, there is the apparent obstruction presented by Bianchi identities to the variability of the Λ term in the Einstein equations, and the fact that this obstacle is promptly removed in the first order formalism if torsion is permitted. That the presence of torsion can change dramatically the perspective of problems is not new (see for example [3][4][5][6][7][8][9][10][11][12][13][14]). In the context of [1] the requisite torsion is provided by a topological term (the Euler invariant) multiplied by an appropriate function of Λ uniquely specified by the Bianchi identities.…”
Section: Introductionmentioning
confidence: 99%